Rehabilitation: A crucial component in the future of HIV care and support - Stephanie Nixon; Lisa Forman; Jill Hanass-Hancock; Muriel Mac-Seing; Norbert Munyanukato; Hellen Myezwa; Chiara Retis (AOSIS, 2011)
Provision of antiretroviral therapy (ART) is not an end in itself but a means to achieving improved wellness for people living with HIV. Rehabilitation, broadly defined, is another key contributor to wellness within this context. Understanding the potential for rehabilitation requires that one is able to consider HIV not only within a biomedical model that focuses on body systems, diagnoses and symptoms, but also within a rehabilitation framework that focuses on how these diagnoses and symptoms affect people's lives more broadly. Furthermore, rehabilitation is a human rights imperative, which deserves the energetic attention enjoyed by other aspects of HIV treatment and care. In particular, the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) is shining a long-overdue spotlight on the human rights imperatives associated with disability. For South Africa and other countries, proactively and meaningfully engaging rehabilitation in the HIV response will require major shifts on several fronts, including practice, education, policy and research. We argue that in settings where ART delivery is now widespread, HIV should be understood not only as a medical issue, but as a rehabilitation and disability concern. Whereas medicine adds years to life, it is rehabilitation that aims to add life to years.